1994
DOI: 10.1177/019262339402200104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Six-Week Exposure to Excess Iodide on Thyroid Glands of Growing and Nongrowing Male Fischer-344 Rats

Abstract: A 6-wk exposure to excess iodide intake (EII) via drinking water (260 mg potassium iodide/L) demonstrated different effects on growing (4-wk old) and nongrowing (45-wk old) male Fischer-344 rats. In growing rats, EII induced a significant increase in thyroid weight, pituitary weight, serum thyroid-stimulating hormone (TSH), and thyroxine (T4). The labeling index (LI) of thyroid follicular cells was slightly increased, although not statistically significant. Histologically, an increase in follicular cell height… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It has also been reported that administration of excess iodide promotes thyroid tumor development in rats initiated with N -bis(2-hydroxypropyl)-nitrosamine (Kanno et al 1992). However, iodide excess alone has not been sufficient in inducing follicular cell hyperplasia and thyroid tumors in rats but more commonly causes hypothyroidism (Backer and Hollowell 2000; Kanno et al 1994). This is believed to be due partly to the escape from the Wolff-Chaikoff effect (acute inhibition of iodine organification) that is seen within days of exposure to excess iodide (Wolff and Chaikoff 1948).…”
mentioning
confidence: 99%
“…It has also been reported that administration of excess iodide promotes thyroid tumor development in rats initiated with N -bis(2-hydroxypropyl)-nitrosamine (Kanno et al 1992). However, iodide excess alone has not been sufficient in inducing follicular cell hyperplasia and thyroid tumors in rats but more commonly causes hypothyroidism (Backer and Hollowell 2000; Kanno et al 1994). This is believed to be due partly to the escape from the Wolff-Chaikoff effect (acute inhibition of iodine organification) that is seen within days of exposure to excess iodide (Wolff and Chaikoff 1948).…”
mentioning
confidence: 99%
“…Pisarev and Itoiz [15] observed that KI decreased the action of TSH and cAMP on thyroid growth and protein synthesis. On the contrary Kanno et al [16] reported that an excess of iodide induced a significant increase in thyroid weight, pituitary weight, serum TSH, and T 4 in growing rats.…”
Section: Thyroid Gland and Proliferationmentioning
confidence: 87%
“…This test measures the accumulation of 125 I in the thyroid gland (phase I), followed by measurement of thyroid: blood 125 I ratio using discharge with perchlorate (phase II). 122 125 In phase I, compounds that inhibit 125 I uptake into the thyroid or organification of 125 I in the gland (eg, NIS and TPO inhibitors) will have lower accumulation of radiolabel in the thyroid gland, whereas compounds that alter TH levels at extrathyroidal sites (eg, by enzyme induction and enhanced T4 metabolism) generally increase the uptake of 125 I into the thyroid gland. Phase II animals are treated with perchlorate which releases unbound 125 I from the thyroid.…”
Section: Other Types Of Supporting Datamentioning
confidence: 99%